Hubungan Pemberian Penguatan (Reinforcement) terhadap Motivasi Belajar Siswa Kelas Tinggi di UPT SD Negeri 79 Ujung Tanah - Julianah Bt. Sanawiah; Satriani DH; Abd. Hafid (STKIP Andi Matappa Pangkep, 2021)
This research is a quantitative research using a correlational design which aims to determine the relation between reinforcement and learning motivation of high-class students at UPT SD Negeri 79 Ujung Tanah Cenrana Sub-district Bone District. The number of samples included the total number of the population. The data collection was carried out in this research by providing a questionnaire. The data analysis technique used a descriptive statistical analysis and inferential statistical analysis. It is obtained that the description of giving reinforcement has an avarage of 55,91% and the percentage is 55,5% include in the less category and the description of student learning motivation has an avarage of 56,45% and the percentage is 56,3% include in the medium category. The result of inferential statistical analysis showed tcount ≥ ttable at a significance level of 5%. Therefore H0 is rejected and H1 is accepted. From the result of the research can be concluded that there was a significance relationship between reinforcement and learning motivation of high-class students at UPT SD Negeri 79 Ujung Tanah Cenran Sub-district Bone District.